2022
DOI: 10.3390/dj10090161
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Enamel Acid Resistance and Whitening Effect of the CAP System

Abstract: This study aimed to compare the effectiveness of a novel professional tooth-strengthening system and a conventional caries-prevention method that involved the use of high fluoride concentrations, to determine whether the system has a whitening effect. Bovine tooth-enamel samples were treated with fluoride gel (conventional APF method) or a mixture of citric acid gel, calcium phosphate (α-TCP), and fluoride gel, referred to as the CAP system; these treatments were performed to generate an acid-resistant layer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
2
2
1
Order By: Relevance
“…Soares et al performed a micro-energy dispersive X-ray fluorescence analysis after applying nHAp and APF gels to the enamel and found that the nHAP-treated group had higher calcium and phosphorus contents than the APF group [ 31 ]. The coatings in our study are consistent with those observed in previous studies; moreover, the thickness in the BioHap group was greater than those observed in previous studies ( Figure 4 f) [ 24 , 31 , 32 , 33 ]. The coating layer is expected to physically protect the tooth surface from acid, and it has been reported to suppress tooth demineralization [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Soares et al performed a micro-energy dispersive X-ray fluorescence analysis after applying nHAp and APF gels to the enamel and found that the nHAP-treated group had higher calcium and phosphorus contents than the APF group [ 31 ]. The coatings in our study are consistent with those observed in previous studies; moreover, the thickness in the BioHap group was greater than those observed in previous studies ( Figure 4 f) [ 24 , 31 , 32 , 33 ]. The coating layer is expected to physically protect the tooth surface from acid, and it has been reported to suppress tooth demineralization [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the Ld in the BioHap group was approximately half of that in the control group ( Figure 7 b). The demineralization pattern in the APF group is consistent with those observed in previous studies; however, localized demineralization under the coating layer, such as that in the BioHap group, has not been observed in previous studies [ 24 ]. The CMR image of the BioHap group quantitatively clarified that demineralization did not extend to deep layers in the BioHap group; instead, it was observed just below the coating layer and enamel surface.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations